The State of Education Funding in Israel - Iris BenDavid-Hadar (Educational Considerations, 2014)
Perspectives on International Education Finance. Israel regards education as an essential part of its infrastructure for national security, competitive ability, and social cohesiveness.
Keywords: Education; funding; instructional hours; Israel; ethnicity; budget; top-performing schools